Theoretical Studies of the Additions of Germylenes to Ethylene - Su, Ming-Der; Chu, San-Yan (Journal of the American Chemical Society, 1999)
Complete geometry optimizations were carried out using density functional theory to study the potential energy surfaces for cycloaddition of germylene to the CC double bond of ethylene. The GeX2 + C2H4 (GeX2 = GeH2, Ge(CH3)2, Ge(NH2)2, Ge(OH)2, GeF2, GeCl2, GeBr2, and GeCH2) systems are the subject of the present study. All the stationary points were determined at the B3LYP/6-31G* level of theory. The major conclusions that can be drawn from this work are as follows:  (i) In contrast to the case of the carbene additions, a π-complex intermediate is formed between germylene and ethylene, which should play a key role in subsequent polymerization. (ii) On the basis of the results of the present study, it is apparent that germylene cycloadditions occur in a concerted, asynchronous manner. (iii) Germacyclopropanes, unlike cyclopropanes, are quite unstable compounds, reverting thermally to their precursors and then polymerizing rapidly, or even reacting with a second molecule of olefin to yield a cyclic compound. (iv) Considering the effect of substitution at the germanium center, our theoretical findings suggest that the cycloaddition of germylene with electropositive and/or bulky substituents is feasible from both a kinetic and a thermodynamic viewpoint. In contrast, germylenes bearing electronegative and/or π-donating substituents will tend not to undergo cycloadditions. Note that this conclusion is based upon the assumption that three-membered-ring germacyclopropane is the unique end product for germylene additions. (v) The cycloadditions of germylenes to alkenes are more endothermic (or less exothermic) than the same reactions of carbenes, reflecting the weaker Ge−C vs C−C bond.